Very high HDL-C (high-density lipoprotein cholesterol) is associated with increased cardiovascular risk in patients with NSTEMI (non-ST-segment elevation myocardial infarction) undergoing PCI (percutaneous coronary intervention) - Lijuan Chen; Yuanyuan Zhao; Zheng Wang; Yifei Wang; Xiangwei Bo; Xiaoxi Jiang; Chunshu Hao; Chengwei Ju; Yangyang Qu; Hongjian Dong (BMC Cardiovascular Disorders, 2023)
Abstract Background Studies in populations with or without cardiovascular disease have shown that very high HDL-C levels are associated with an increased risk of cardiovascular events. However, the exact relationship between HDL-C levels and long-term prognosis remains unknown in patients with myocardial infarction (MI) undergoing percutaneous coronary intervention (PCI). Methods This was a post hoc secondary analysis of long-term follow-up results in patients undergoing PCI open-label, observational cohort study. Patients with MI who had undergone PCI were enrolled. Restricted cubic spline (RCS) analysis and logistic regression analysis were performed to assess the relationship between HDL-C levels and the risk of cardiovascular events. Results A total of 1934 patients with MI undergoing PCI were enrolled in our analysis and our population was divided in 3 groups according to the HDL-C plasma levels: HDL-C < 40 mg/dL (low HDL-C); HDL-C between 40 and 80 mg/ dL (medium HDL-C); and HDL-C > 80 mg/dL (high HDL-C). RCS analysis showed a nonlinear U-shaped association between HDL-C levels and major adverse cardiac and cerebrovascular events (MACCE) in patients with NSTEMI with adjusted variables. After adjusting for potential confounders, the follow-up analysis indicated that high risk group had elevated occurrence of MACCE than low risk group (HDL-C 35 and 55 mg/dL) (OR:1.645, P = 0.006). Conclusions Our analysis demonstrated that there is a U-shaped association between HDL-C and MACCE in patients with NSTEMI undergoing PCI.